2016
DOI: 10.1186/s12874-016-0265-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of in-hospital mortality following major lower extremity amputations in type 2 diabetic patients using artificial neural networks

Abstract: BackgroundOutcome prediction is important in the clinical decision-making process. Artificial neural networks (ANN) have been used to predict the risk of post-operative events, including survival, and are increasingly being used in complex medical decision making. We aimed to use ANN analysis to estimate predictive factors of in-hospital mortality (IHM) in patients with type 2 diabetes (T2DM) after major lower extremity amputation (LEA) in Spain.MethodsWe design a retrospective, observational study using ANN m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
(51 reference statements)
1
23
0
Order By: Relevance
“…However, previous studies that have utilized it either did not generate it as a summary tool or had small sample sizes to achieve valid results [3,34,35]. Whilst other studies have shown its association with either short-or longterm mortality after major LEA [4,29,36,37]. Adding to the existing evidence, our study has shown ACCI to be a signi cant predictor of both short-term and long-term mortality after major LEA even after adjusting for sex, age, levels of amputations, and type of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies that have utilized it either did not generate it as a summary tool or had small sample sizes to achieve valid results [3,34,35]. Whilst other studies have shown its association with either short-or longterm mortality after major LEA [4,29,36,37]. Adding to the existing evidence, our study has shown ACCI to be a signi cant predictor of both short-term and long-term mortality after major LEA even after adjusting for sex, age, levels of amputations, and type of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in life expectancy of patients diagnosed with T2DM has also increased the associated morbidity [4]. Advanced age, African ethnicity and male sex are associated with an increased risk of amputations in patients with T2DM, while other factors such as female gender, kidney failure and congestive heart failure increase the risk of death during hospitalization [5]. In addition, undergoing a MA is a significant risk factor for long term mortality among T2DM patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…In-hospital mortality due to amputations remained stable between 2001 and 2012, around 10%, resulting in an economic cost of 33% of the total cost spent in hospital treatment of T2DM complications [8]. Although there are several published works in relation to nontraumatic amputations in Spain [5][6][7][8], they account for the major and minor procedures globally in the analysis, or do not differentiate the type of diabetes. To our knowledge, there are no publications that have compared MA incidence in patients with T2DM in the seventeen Autonomous Communities (AACC) or Regions of Spain, nor analyzed possible regional heterogeneity in MA mortality or days of hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Advanced age, African ethnicity and male sex are associated with an increased risk of amputations in patients with T2DM, while other factors such as female gender, kidney failure and congestive heart failure increase the risk of death during hospitalization. [5] In addition, undergoing a MA is a significant risk factor for long term mortality among T2DM patients. [6] The overall incidence of amputations due to diabetes increased by 4.29% in Spain between 2001 and2004, followed by a downward trend until 2012, around 2%.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In-hospital mortality due to amputations remained stable between 2001 and 2012, around 10%, resulting in an economic cost of 33% of the total cost spent in hospital treatment of T2DM complications. [8] Although there are several published works in relation to non-traumatic amputations in Spain [5][6][7][8], they account for the major and minor procedures globally in the analysis, or do not differentiate the type of diabetes. To our knowledge, there are no publications that have compared MA incidence in patients with T2DM in the seventeen Autonomous Communities (AACC) or Regions of Spain, nor analyzed possible regional heterogeneity in MA mortality or days of hospital stay.…”
Section: Introductionmentioning
confidence: 99%